An analysis of nearshore profile and bar development under large scale erosive and accretive waves. Issue 2 (4th March 2018) - Sanchez-Arcilla, Agustin; Caceres, Ivan
ABSTRACT: Typical morphodynamic laboratory tests have been carried out at small scales and without sufficient coverage or resolution. These limitations, applying particularly to accretive tests, have obstructed reliable observations and restricted modelling capabilities. Here we present experiments with erosive/accretive waves acting on a large scale flume bed profile. The paper reports a set of high-quality hydro-morphodynamic data. The analysis is focused on net transport rates and how these patterns change between different accretive conditions. The measured velocity and acceleration skewness are presented and discussed, linking the net transport over the bar to the measured hydrodynamics and sediment concentrations. The resulting profile behaviour is discussed as a function of hydro-morphodynamic settings to facilitate comparisons with other datasets.